(untitled) (Journal of Governance and Development (JGD), 2008)
This paper is about Malaysian regulation with regard to the issue of media freedom. Malaysia has many laws that restrict the function of the media, either printing media, broadcasting media or the Internet. The sources of the restriction can be found in Federal Constitution and many laws such as the Internal Security Act, Sedition Act, Printing Presses and Publications Act, and others. This restriction is actually limiting the degree of democracy practised in this country. With the cases listed, this paper is in the intention to expose the limitation of media freedom in Malaysia.